Interactions between human milk oligosaccharides, microbiota and immune factors in milk of women with and without mastitis - Irma Castro; Cristina García-Carral; Annalee Furst; Sadaf Khwajazada; Janneiry García; Rebeca Arroyo; Lorena Ruiz; Juan M. Rodríguez; Lars Bode; Leónides Fernández (Scientific Reports, 2022)
Abstract Lactational mastitis is an excellent target to study possible interactions between HMOs, immune factors and milk microbiota due to the infectious and inflammatory nature of this condition. In this work, microbiological, immunological and HMO profiles of milk samples from women with (MW) or without (HW) mastitis were compared. Secretor status in women (based on HMO profile) was not associated to mastitis. DFLNH, LNFP II and LSTb concentrations in milk were higher in samples from HW than from MW among Secretor women. Milk from HW was characterized by a low bacterial load (dominated by Staphylococcus epidermidis and streptococci), high prevalence of IL10 and IL13, and low sialylated HMO concentration. In contrast, high levels of staphylococci, streptococci, IFNγ and IL12 characterized milk from MW. A comparison between subacute (SAM) and acute (AM) mastitis cases revealed differences related to the etiological agent (S. epidermidis in SAM; Staphylococcus aureus in AM), milk immunological profile (high content of IL10 and IL13 in SAM and IL2 in AM) and milk HMOs profile (high content of 3FL in SAM and of LNT, LNnT, and LSTc in AM). These results suggest that microbiological, immunological and HMOs profiles of milk are related to mammary health of women.